SMARTMA CONTROLING AN IMPROVING RICE PEST REMOVAL - Mahrizal Masri; Hermansyah Alam (Jurnal Scientia, 2023)
The increasingly rapid human growth requires food, but the expansion of land for farming is decreasing and farmers can no longer afford the necessary farming equipment such as fertilizers and pesticides to control plant pests, so efficient plant processing techniques are very necessary, in this case plants paddy. This paper discussed about increase crop yields, controlling pests in rice plants is also very important. Pests are enemies of rice farmers, especially leafhoppers which attack young rice plants and stinging grasshoppers which attack rice plants when the rice has started to grow young grains. Until now, farmers still rely on the use of chemical pesticides which are relatively expensive, and The economic needs of farmers are increasing, so farmers are also looking for fast and cheap without paying attention to the health impacts on humans who consume the rice.